Intellectual Capital, Company Size, Liquidity and Capital Structure in Their Effect on Firm Value with Profitability as a Mediator - Angelicia; Ikhsan, Syarbini; M. Helmi, Syarif (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to analyze the influence of intellectual capital, firm size, liquidity, and capital structure on firm value, with profitability as a mediating variable. The research focuses on consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The analysis is conducted using multiple linear regression and the Sobel test to measure both direct and mediating effects. The results indicate that intellectual capital has a significant positive effect on profitability, while firm size and liquidity do not show a significant impact. Capital structure has a significant negative effect on profitability. Additionally, intellectual capital and capital structure significantly influence firm value, whereas firm size and liquidity do not. Profitability is proven to mediate the effect of intellectual capital and capital structure on firm value but does not mediate the relationship between firm size and liquidity and firm value. These findings support the Resource-Based Theory (RBT), which highlights the importance of managing strategic resources to create added value, and the Signaling Theory, which suggests that profitability and capital structure provide positive signals to investors regarding firm performance. The study implies that companies should prioritize managing intellectual capital and capital structure to enhance profitability, ultimately increasing firm value. Future research is recommended to extend the study period and consider external variables, such as macroeconomic conditions, for more comprehensive insights.